An engineered solution to multi-physics of insulated gate bipolar transistor module considering electrical-thermal-mechanical coupling effect. (January 2023) - Feng, S.Z.; Guo, Y.C.; Królczyk, Grzegorz; Han, Xu; Incecik, Atilla; Li, Zhixiong
Highlights: Multi-physics analysis of Insulated Gate Bipolar Transistor is carried out. The modeling complexity can be well reduced through the proposed approach. Accurate multi-physics responses of IGBT module can also be calculated. Good balance between the computing cost and calculating accuracy has been achieved. Abstract: A computational approach is developed for multi-physics modelling of Insulated Gate Bipolar Transistor (IGBT) module considering the electrical-thermal-mechanical coupling effect. In this approach, the tetrahedral elements are used to build the finite element domains of an efficient IGBT model. Then, the discretized system equations of the IGBT model are obtained from the gradient smoothing technique and Galerkin weak form to describe the interaction between the electrical-thermal-mechanical coupling fields. In addition, stabilization items considering the variance of the electric field intensity, temperature gradient and strain gradient are also introduced when constructing the discrete system equations. Numerical evaluation is carried out to fully examine the validity of this method for the electrical-thermal-mechanical coupling analysis of IGBT module. The obtained results demonstrate that, when using the same tetrahedral mesh, the present approach is able to generate much higher accuracy, convergence and computing efficiency than the popular finite element method (FEM) methods. As a result, a good balance between the computing cost and calculating accuracy has been achieved by the proposed method to provide an efficient tool for the IGBT multi-physics coupling problem.